EFFECTS OF ARTIFICIAL ACCELERATED AGING ON THE OPTICAL PROPERTIES OF RESIN COMPOSITES - Barbosa Dantas, Debora Cristina [UNESP]; Mathias, Ingrid Fernandes [UNESP]; Borges, Alessandra Buhler [UNESP]; Gomes Torres, Carlos Rocha [UNESP]; Ferraz Caneppele, Taciana Marco [UNESP] (Univ Federal Uberlandia, 2018)
The aim of this study was to evaluate the effects of ultraviolet artificial aging on color, fluorescence, gloss, and translucency of different composite resins. Seventy-five cylindrical-shaped specimens (6 mm in diameter and 1 mm thick) of four different composites: Admira Fusion (VOCO), TPH3 (DENTSPLY), GrandioSO (VOCO) and Filtek (TM) Z350 XT (3M/ESPE), were built. Enamel samples obtained from bovine incisors were prepared with the same dimensions and used as a control group. Assessments of color, translucency, fluorescence, and gloss were performed at baseline and after artificial aging. Specimens were immersed in artificial saliva and submitted to artificial aging (UV light for 300h). Data were analyzed using one-way ANOVA and Tukey's post hoc test (alpha = 0.05). After aging, all resin composites presented significant alterations, mainly Filtek (TM) Z350 XT. Fluorescence decreased in all resin composites and enamel. Gloss was reduced in all groups, too, with major rates for TPH3 and GrandioSO, which was similar to the enamel reduction. Translucency did not present a significant difference for the resin composites, although there was a reduction in the enamel. After artificial aging resin composites became darker, less fluorescent, less glossy, and with no alteration in translucency.
Keywords: Composites; Enamel; Aging; Color; Translucency; Fluorescence; Gloss